Redenomination: Why is It Effective in One Country but Not in Another? - Karnadi, Erwin Bramana; Adijaya, Putu Rusta (International Journal of Economics and Financial Issues, 2017)
The real impact of redenomination is still an on-going debate in the academic world. Redenomination is process decreasing values of a currency without changing its real currency exchange rate. In this research, we are using a panel data set obtained from The World Bank to estimate the impact of redenomination on macroeconomic variables such as inflation rate, real GDP per capita and real currency exchange rate. We decided to use fixed effects estimators to take into account the impact of specific characteristics of each country. We concluded that redenomination can significantly decrease estimated inflation rate and increase estimated real GDP per capita. We also concluded that redenomination has no significant impact on estimated real currency exchange rate. However, the effectiveness of redenomination depends on the country’s government effectiveness and political stability which will improve country’s economic conditions and their competitiveness. Keywords: fixed effects estimators, redenomination JEL Classifications: C5, E0, E5